RANCANGAN LEAFLET BIOLOGI KELAS X SMA PADA MATERI PROTISTA - Rahayu Srikandi; Zulfarina Zulfarina; Nursal Nursal (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: Efforts to increase student interest are with interesting learning media, one of which is Leaflet learning media. This study aims to determine the potential of leaflet design in high school learning for class X Protista material. This research was conducted at the Binawidya Campus, Riau University in August-December 2020. This research was carried out with the ADDIE design, namely the analysis and design stages. The analysis stage is carried out by analyzing the curriculum and analyzing the syllabus issued by the 2013 revised 2018 Ministry of Education and Culture. The design stage consists of designing learning tools, in the form of syllabus, lesson plans and designing leaflets consisting of: Cover, Title of Basic Competence / Main Materials to be achieved, Supporting Information, Learning Resources and Assignments and Assessments. Based on the potential analysis, it was found that the leaflet design for Protista class X KD 3.6. and KD. 4.6 can be used as an alternative learning media. Keywords: Leaflet, Learning Media, Protists.Kata Kunci : Leaflet, Learning Media, Protists